Comprehensive Midwifery Care for Mrs. S G3P2A0 at Cipeundeuy Public Health Center, West Bandung Regency - Nursiam, Rahma; Yuliana; Puspita, Ameliana; Sutari, Sri (STIKes Budi Luhur Cimahi, 2026)
Frequent urination is one of the common discomforts experienced by pregnant women in the third trimester and can affect sleep quality as well as daily activities. The World Health Organization (WHO) reports that approximately 50% of third-trimester pregnant women experience an increased frequency of urination. Data from the Indonesian Ministry of Health in 2022 show a prevalence of 72%. At the Cipeundeuy Public Health Center, West Bandung Regency, an increase in complaints of frequent urination among third-trimester pregnant women was also observed. One non-pharmacological intervention that can be applied to address this complaint is prenatal exercise, which aims to strengthen the pelvic floor muscles and improve bladder control. This study aimed to describe comprehensive midwifery care for Mrs. S (G3P2A0) with complaints of frequent urination at the Cipeundeuy Public Health Center, West Bandung Regency. The study employed a descriptive case study design. The main intervention was video-based prenatal exercise performed regularly for 30 minutes per session. Data were collected through observation and the mother’s subjective reports before and after the intervention. The results showed a decrease in the frequency of urination from a high category to a normal category. The mother also reported improvements in sleep quality and increased comfort in carrying out daily activities. In conclusion, video-based prenatal exercise has the potential to help reduce complaints of frequent urination in third-trimester pregnant women. However, as this study was a single case study, the results cannot be generalized, and further research with a larger sample size is required.